Predicting the stacking fault energy of austenitic Fe-Mn-Al (Si) alloys - Choi, Young Won; Dong, Zhihua; Li, Wei; Schönecker, Stephan; Kim, Hansoo; Kwon, Se Kyun; Vitos, Levente (Materials & design, 2020)
Aluminum and silicon are common alloying elements for tuning the stacking fault energy (SFE) of high Mn steels. Today the theoretical investigations on the Fe-Mn-Al/Si systems using Density Functional Theory (DFT) are very scarce. In the present study, we employ a state-of-the-art longitudinal spin fluctuations (LSFs) model in combination with DFT for describing the magnetic effects in Fe-Mn based alloys at finite temperature. We find that the traditional DFT-floating spin results fail to explain the experimental trends. However, the DFT-LSFs approach properly captures the Al-induced increase and Si-induced decrease of the SFE of the base alloy in line with the room-temperature observations. This finding highlights the importance of LSFs in describing the Al/Si effects on the SFE of Fe-Mn based alloys. We point out that the effects of the non-magnetic Al and Si additions on the SFE are in fact determined by the magnetic state of the host matrix. In addition, we estimate the role of carbon addition in the alloying effects of Al and Si. The present results provide a convenient pathway to access the important mechanical parameters for designing advanced high-strength alloys. [Display omitted] •Traditional floating spin models fail to account for the experimental trends.•Longitudinal spin fluctuations yield stacking fault energies in good agreement with experiments.•The magnetic state of the host Fe-Mn alloy is determinative for the alloying trends on the stacking fault energy.